Study of the constituents of the leaves of Nerium indicum Miller (Fam. Apocynaceae) - Gregorio, Gisela P.
The leaves of Nerium indicum Miller (Fam. Apocynaceae) was examined for glycosides and four compounds with a maximum absorbance at 222 nm, 276 nm, and 280 nm. were isolated.